Analisis dampak pembelajaran daring pada keterampilan membaca pemahaman cerita fiksi peserta didik kelas iv sekolah dasar - Senja, Puti Alleza Kemuning; Winarni, Retno; Daryanto, Joko (Didaktika Dwija Indria, 2022)
This study aims to describe the analysis of the impact of online learning on reading comprehension skills. This research uses descriptive qualitative research methods. The subjects of this study were fourth grade students of SD Negeri 6 Parakan. Research data collection is done through data collection techniques of observation, interviews and document studies. The data analysis technique uses the Miles and Huberman model which consists of data reduction, data presentation and conclusion drawing. The results showed that the fourth grade students of SD Negeri 6 Parakan in analyzing reading comprehension skills in fiction stories were still less successful in obtaining reading information, explaining the intrinsic elements of reading, drawing conclusions from the reading, and determining statements that were in accordance with the contents of the reading. from reading. Constraints in reading comprehension skills are the students' lack of interest in reading, lack of reading facilities and the role of parents. The solution to these problems is to foster students' interest in reading, improve reading facilities both at school and at home, and get used to reading from an early age by parents.